The Transformation of Tourist Villages in the Digital Era: Innovative Strategies to Enhance Tech-Based Tourism Appeal - Haryono, Joko (Arbain Publishing, 2025)
The rapid advancement of digital technologies has significantly reshaped various industries, with tourism being one of the most affected sectors. This study explores the transformation of tourist villages in the digital era, focusing on innovative strategies aimed at enhancing the appeal of tech-based tourism. By integrating digital tools such as virtual reality (VR), augmented reality (AR), mobile applications, and social media, tourist villages are increasingly able to attract tech-savvy travelers and offer immersive experiences. This paper examines the role of these digital innovations in revitalizing traditional tourist villages, improving visitor engagement, and creating new revenue streams. Additionally, it highlights how these technologies help preserve cultural heritage while offering modern solutions for marketing and customer service. The findings suggest that the digital transformation of tourist villages not only enhances their competitiveness in the global tourism market but also facilitates sustainable tourism practices. Ultimately, the study provides a comprehensive overview of the key strategies that can be adopted by local stakeholders to ensure the long-term success and sustainability of tourist villages in the digital age.